Have we become indifferent to the whispers of loss? A forensic pathologist’s perspective - Kattamreddy, Ananth Rupesh (Research and Humanities in Medical Education, 2024)
Editor's note: This issues with the consent of the author. In keeping with the journal's desire to avoid ableist terminology, the title of this narrative has changed from "Have we turned a deaf ear to the whispers of loss? A forensic pathologist’s perspective" to "Have we become indifferent to the whispers of loss? A forensic pathologist’s perspective" as of 7th April, 2024.